Plant factory using artificial light : adapting to environmental disruption and clues to agricultural innovation - Anpo, Masakazu, 1946-; Fukuda, Hirokazu; Wada, Teruo (Elsevier, 2019)
Plant Factory Using Artificial Light: Adapting to Environmental Disruption and Clues to Agricultural Innovation features interdisciplinary scientific advances as well as cutting-edge technologies applicable to plant growth in plant factories using artificial light. The book details the implementation of photocatalytic methods that ensure the safe and sustainable production of vegetables at low cost and on a commercial scale, regardless of adverse natural or manmade influences such as global warming, climate change, pollution, or other potentially damaging circumstances. Plant Factory Using Artificial Light is an essential resource for academic and industry researchers in chemistry, chemical/mechanical/materials engineering, chemistry, agriculture, and life/environmental/food sciences concerned with plant factories.